Changes in Infrastructure and Social Structure in Lubuklinggau during the Colonial Period (1934-1942) - Sarkowi Sarkowi; Ira Miyarni Sustianingsih; Yadri Irwansyah; Abadi (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The city of Lubuklinggau experienced various significant changes during the Dutch colonial administration, particularly in terms of infrastructure and social structure. The period between 1934 and 1942 marked a crucial phase that demonstrated a close interaction between colonial interests and local dynamics. This study aims to examine the transformation of infrastructure and changes in social structure that occurred in Lubuklinggau within the context of Dutch colonialism. This research employs a historical method with a descriptive qualitative approach. Data were obtained through archival studies, official colonial documents, and relevant secondary literature, and were analyzed using an interpretative approach to reconstruct the social dynamics and infrastructure development of the time. The validity of the data was tested through source criticism techniques commonly used in historical research. The findings reveal that the construction of railway lines and supporting facilities encouraged the process of urbanization and increased social mobility among the people of Lubuklinggau. Furthermore, the emergence of new social classes as a result of colonial economic policies indicates a gradual shift in the social structure. This transformation reflects the colonial strategy to integrate the hinterland into the colonial politico-economic system. These findings contribute to a deeper understanding of local history in the broader context of global colonial influence.